Perancangan Sistem Pemesanan Makanan Menggunakan QR-CODE dan Linear Search Berbasis Web - Asep Sunan Ali; Septi Andryana; Ira Diana Sholihati (LPPM STIKI MALANG, 2023)
Technological advances in the field of mobile applications for online purchases, especially those involving food and beverages, have grown significantly in the current era of globalization. To overcome this problem, the reviewer uses QR code scanning technology. This QR code technology was chosen because it can offer a very fast, simple, precise and mechanical data collection method. The purpose of designing this application is to make it easier to order food and drinks using QR-codes. In this study using the Linear Search Algorithm method as a search for food and beverage data. Linear Search works on unordered or ascending text sequences. he looks for data by comparing one by one the elements of a set, write them in a table or array, by starting the search on the first element in the sequence of a set. From the results of the tests that have been carried out, it can be seen that the earlier the position of the food and beverage menu data that is being searched for, the longer the program will take to find the intended data, the faster it will be. Meanwhile, the later the data menu position you are looking for, the longer the program execution time will be. Here proves that the index position of the data you are looking for is very influential on the speed of searching for the data. So that the average value is obtained as follows, the data is in the initial position 0.25 seconds, the middle position is 0.27 seconds, the final position is 0.29 seconds. While the use of memory that is used both eat the same memory storage, which is 523kb.